Early Advanced LIGO binary neutron-star sky localization and parameter estimation. (May 2016) - Berry, C P L; Farr, B; Farr, W M; Haster, C-J; Mandel, I; Middleton, H; Singer, L P; Urban, A L; Vecchio, A; Vitale, S; Cannon, K; Graff, P B; et al.
Abstract: 2015 will see the first observations of Advanced LIGO and the start of the gravitational-wave (GW) advanced-detector era. One of the most promising sources for ground- based GW detectors are binary neutron-star (BNS) coalescences. In order to use any detections for astrophysics, we must understand the capabilities of our parameter-estimation analysis. By simulating the GWs from an astrophysically motivated population of BNSs, we examine the accuracy of parameter inferences in the early advanced-detector era. We find that sky location, which is important for electromagnetic follow-up, can be determined rapidly (∼ 5 s), but that sky areas may be hundreds of square degrees. The degeneracy between component mass and spin means there is significant uncertainty for measurements of the individual masses and spins; however, the chirp mass is well measured (typically better than 0.1%).